Prediction of Climate Change Impacts on the Distribution of an Umbrella Species in Western Sichuan Province, China: Insights from the MaxEnt Model and Circuit Theory - Xiaoyun Deng; Qiaoyun Sun (Diversity)
Climate change poses a significant threat to biodiversity. Predicting the impacts of climate change on species distribution and dispersal through computational models and big data analysis can provide valuable insights. These predictions are crucial for developing effective strategies to mitigate the threats that climate change poses to biodiversity. Our study investigated the potential impact of climate change on an umbrella species (Ursus arctos pruinosus) in Western Sichuan Province, China. We employed the MaxEnt and Circuit Theory to assess both the current and potential future shifts in the distribution and migration corridors. The results indicated that climate and environmental factors had the greatest influence on species distribution, with bioclimatic variables bio12, bio3, and elevation contributing 22.1%, 21.5%, and 19.3%, respectively. Under current climatic conditions, the total suitable habitat area for the species was 70,969.78 km2, with the largest suitable habitats located in Shiqu and Litang, accounting for 24.39% and 15.86% of the total area, respectively. However, under future climate scenarios, predictions for RCP 2.6, RCP 4.5, and RCP 8.5 showed a significant reduction in suitable habitat area, ranging from 7789.26 km2 to 16,678.85 km2. The Yajiang and Xinlong counties experienced the most severe habitat reductions, with declines exceeding 50%. Additionally, the altitudinal distribution of suitable habitats shifted, with suitable habitats gradually moving to higher elevations under future climate scenarios. Our study also analyzed the species’ dispersal paths. Under current climatic conditions, the dispersal paths predominantly followed a northwest-to-southeast orientation. However, by the 2070s, under all three RCPs, dispersal resistance is projected to significantly increase, the density of dispersal paths will decrease, and the connectivity of these paths will be reduced. In the most extreme RCP 8.5 scenario, southern dispersal paths nearly disappeared, and the dispersal paths contracted towards the northwest. These findings highlight potential threats posed by climate change to the species’ habitats and dispersal corridors, emphasizing the importance of considering both current and future climate change in conservation strategies to protect this vulnerable species and its ecosystem.